DESIGN OF CARGO BERTH STRUCTURE WITH PRECAST CONCRETE CONSTRUCTION IN THE PORT OF KETAPANG, WEST KALIMANTAN - Florival Java Sungga P, Sabinus
Indonesia is one of the largest maritime countries in the world. Therefore, the ability and connection between islands and regions is highly demanded for the smooth activities of the economy, industry, and development in other fields. Kalimantan as one of the largest islands in Indonesia with abundant natural products, of course the distribution process and economy runs very quickly there. By seeing that the Kalimantan region is dominated by forests and rivers, it becomes the basis of the design of cargo berth in Ketapang Regency, West Kalimantan Province, as a node for water transportation facilities. In this final project case study on cargo berth planning with precast concrete construction at Ketapang Port, West Kalimantan, will provide exposure to the design of the berth structure and trestle structure based on design criteria used, such as a condition of structural planning taking into account the environmental conditions at the study site. This final project includes the calculation of berth and trestle dimensions, structural modeling, structural element looping design, precast concrete construction design, and soil capacity. Berth structures are designed using precast concrete construction because it has many advantages over conventional concrete. The design of structural elements with precast concrete includes analysis of lifting conditions, installations and pedestals. All structural elements are designed in such a way as to form a monolithic structure. The structure analysis is performed use SAP2000 software to determine the reliability of the structure to the loads working on the structure. The results of modeling include unity check ratio (UCR), structural deflection, inner force, and berth structural element building reactions. The style in the structural elements of the berth obtained from the modeling results is used as the basis for the design of the reinforcement of the structural elements. The results of the final project such as the design of the berth and trestle which includes the dimensions of the structure and dimensions of structural elements, the details of the reinforcement of elements based on the inner force, and the depth required for the planting of the pipe foundation in order to withstand structural reactions based on geotechnical data. The design berth has a length dimension of 75 m with a width of 15 m for the main berth structure, and a length of 65 m with a width of 5 m for the trestle structure. Both structures have the same floor elevation of 4 m from LWS. The structural elements on the pier consist of plates, beams, pile caps, and piles. Based on the optimum structure design, a 500 mm diameter steel pipe is used with a thickness of 11 mm on the main berth structure and a diameter of 400 mm with a 10 mm thickening on the trestle structure. On the main berth structure the pipes needs to be planted to a depth of 33 m below the bottom of the water, while on the trestle structure it needs to be planted to a depth of 24 m below the bottom of the water.